Association between serum vitamin D status and the anti-seizure treatment in Chinese children with epilepsy - Dong, Na; Guo, Hong-Li; Hu, Ya-Hui; Yang, Jiao; Xu, Min; Ding, Le; Qiu, Jin-Chun; Jiang, Zhen-Zhou; Chen, Feng; Lu, Xiao-Peng; Li, Xiao-Nan (Frontiers in Nutrition, 2022)
Objective To compare the serum 25-OH-VitD levels, the major marker of vitamin D (VitD) status, between healthy children and children with epilepsy before initiation of and during anti-seizure medications (ASMs) treatment and to evaluate the potential influence factors on 25-OH-VitD levels. Another major aim was to assess the potential role of VitD supplementation. Methods For comparison, we finally enrolled and collected data from 6,338 healthy children presenting to Health Care Department and 648 children visiting primary care pediatricians with symptoms of epilepsy in Children’s Hospital of Nanjing Medical University from January 2019 to June 2021. The demographic and biochemical characteristics of each child were extracted from the hospital information system. Results Serum 25-OH-VitD levels in 648 children with epilepsy were significantly lower than those of 6,338 healthy children (P < 0.0001), and the percentage of VitD insufficiency and deficiency status in pediatric patients was 49.19%. Of note, the serum 25-OH-VitD levels in children with newly diagnosed epilepsy before receiving any ASMs treatment were also significantly lower than those in healthy controls. Interestingly, ASMs therapy, alone or in combination, did not consistently reduce baseline serum VitD levels in children with epilepsy. The lower serum VitD levels in pediatric patients than those in healthy children might be related to the disease itself, rather than the ASMs treatment. As expected, VitD supplementation substantially increased the serum 25-OH-VitD levels (P < 0.0001). More critically, children with epilepsy receiving VitD supplementation achieved good seizure control in our study. Significance In this retrospective study, the childhood epilepsy before initiation of and during ASMs treatment decreased the serum 25-OH-VitD concentrations, suggesting a clear association between epileptic disease and the risk of VitD deficiency. ASMs coadministration and long-term valproic acid treatment did not worse VitD-deficiency status, but in the small group receiving VitD supplementation, there was a significant improvement in reduction of seizure frequency. Therefore, pediatric clinicians are urged to raise public awareness of epilepsy-associated VitD deficiency.